25 years of field exposure of pre-cracked concrete beams; combined impact of spacers and cracks on reinforcement corrosion. (7th June 2021) - Geiker, Mette; Danner, Tobias; Michel, Alexander; Belda Revert, Andres; Linderoth, Oskar; Hornbostel, Karla
Graphical abstract: Highlights: Increased ingress at cracks in 25 years old marine concrete. Severe corrosion in connection with plastic spacers, none or negligible at cracks. Corrosion at the "weakest link" appears to protect the remaining steel. Abstract: The state of corrosion of three pre-cracked concrete beams was investigated after 25 years of marine exposure (atmospheric, tidal and submerged). The influence of inadequate plastic spacers was found to overrule the possible impact of bending cracks on reinforcement corrosion. Increased chloride ingress was detected in cracked areas, but very little corrosion was observed where cracks reached the reinforcement. Also, high chloride content was measured in uncracked parts of the beams, but no or very limited corrosion was observed outside spacers and a few cracks. It is hypothesised that corrosion, initiated early at weak spots (here at plastic spacers) can protect the remaining reinforcement from corrosion.